PERFORMANCE OF MICRO SMALL MEDIUM ENTERPRISES (MSMEs) IN SUPPORTING THE TOURISM SECTOR - Erita Rosalina; Nanang Wahyudin (Integrated Journal of Business and Economics (IJBE), 2021)
This research is about measuring the performance of MSMEs with a balanced scorecard using four perspectives, financial perspective, customer perspective, internal business perspective, learning, and growth perspective. This study will distribute questionnaires to 100 samples of small and medium industries in Pangkalpinang. Based on the results of the balanced scorecard, it is seen from a financial perspective, a customer perspective, an internal business process perspective, a learning, and growth perspective. From the results, it was found that the MSME business actors in Pangkalpinang were in the range of 0-30 million on average, none of which was above 30 million profit. The number of new customers at MSME business stores in Pangkalpinang averaged in the range of 50-60 people during 2019, while for the number of customers from the beginning to the beginning of 2019 the average was in the range of 100-300 people. From the perspective of internal business processes carried out by each MSME business cluster, they provide good services and facilities to customers. Business actors provide the best for customer convenience so that customers are satisfied when making transactions at their place. The learning and growth perspective carried out by each MSME business cluster during 2019 has never increased the skills of its employees so that the absence of training provided cannot have an impact on improving employee work attitudes.